Ceramic bonded WC hard alloy and preparation method thereof

Through one-step mechanical alloying and SPS sintering technology, ceramic-combined WC cemented carbide is prepared, which solves the problems of high production costs and high sintering temperature in the traditional method, and achieves high performance and low cost cemented carbide preparation.

CN119751071APending Publication Date: 2025-04-04YANSHAN UNIV

Patent Information

Application Number
CN202510037337.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The prior art lacks WC cemented carbides combined with ceramics and traditional methods for preparing cemented carbides, which have high production costs and high sintering temperatures, which affect material performance.

Method used

The one-step mechanical alloying (MA) method is used to mix W, Ti, Zr and C powders, and ceramic-bound WC cemented carbide is prepared by discharge plasma sintering (SPS) technology. The vacant position in the system can reduce the sintering temperature and simplify the process.

Benefits of technology

It realizes the efficient preparation of WC cemented carbide with ceramics, reduces production costs, improves the hardness, fracture toughness and corrosion resistance of the material, and simplifies the process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751071A_ABST
    Figure CN119751071A_ABST
Patent Text Reader

Abstract

The invention discloses a ceramic bonded WC hard alloy and a preparation method thereof, WC hard alloy powder is prepared from W powder, Ti powder, Zr powder and C powder, the mass fraction of the W powder is 85-90 wt.%, the mass fraction of the Ti powder is 2-2.5 wt.%, the mass fraction of the Zr powder is 4-4.5 wt.%, and the mass fraction of the C powder is 6-6.5 wt.%. The W powder, the Ti powder, the Zr powder and the C powder are mixed in a mechanical alloying (MA) mode through a one-step method, the novel high-entropy ceramic combined WC hard alloy composite material is prepared through the SPS sintering technology, the sintering temperature is reduced through vacancy energy in a system, sintering is promoted, introduction of oxygen is reduced, the hardness, fracture toughness, corrosion resistance and other performance of a sintered body are improved, and the service life of the high-entropy ceramic combined WC hard alloy composite material is prolonged. Meanwhile, the technological process is simplified, and the production cost of the hard alloy material is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal composite materials, and in particular relates to a ceramic-bonded WC hard alloy and a preparation method thereof. Background Art

[0002] Tungsten carbide has excellent properties such as high melting point (2800℃), high hardness (20-25GPa), low friction coefficient, high electrical and thermal conductivity, strong corrosion resistance and wear resistance, and has become an important industrial material used and studied by people. As a new type of cemented carbide, non-metallic binder phase cemented carbide has better polishing, higher hardness, deformation resistance and corrosion resistance compared with traditional tungsten cobalt cemented carbide. However, the high melting point and low self-diffusion coefficient of tungsten carbide make it extremely difficult to sinter. Chen Linbo et al. found that the hardness of non-bonded phase WC-based cemented carbide increases with the increase of VC and TiC content, while the fracture toughness is the opposite. When the sintering temperature is 1650℃ and the molar content of VC and TiC is 5%, the hardness of the cemented carbide reaches the maximum value, HV is 2533.4, the fracture toughness is the lowest, KIC is 6.85MPa·m1 / 2 [Chen Linbo, Li Changsheng, Zhang Shuai, Li Jianfeng. Research on the influence of VC and TiC on the friction and wear properties of non-binder phase tungsten carbide-based cemented carbide [J]. Rare Metals and Cemented Carbides, 2019, 47(01): 74-79.]. With the further development of the research process, it was found that the sintering temperature of non-stoichiometric TiCx is low and the sintering density is good. The excess titanium in TiCx causes a large number of carbon vacancies in the binder, which promotes the migration of high-temperature substances under high temperature and high pressure conditions, making the material more dense [Jia Xiu. Research on the performance of non-stoichiometric TiCx and refractory compound solid phase sintered body [D]. Yanshan University, 2014]. Zou Qin invented a method for preparing a tungsten carbide composite material without a metal binder phase. The composite material is WC, TiC 0.4 and VC (or NbC, or TaC) ternary composite material, the present invention utilizes TiC 0.4The vacancies in the tungsten carbide can reduce the sintering temperature and promote sintering. On this basis, it can be sintered with tungsten carbide and other transition refractory carbides to form a tungsten carbide composite material without a metal binder, overcoming the shortcomings of traditional WC cemented carbide that softens at high temperature and causes performance failure, while improving its hardness and fracture toughness, and solving the problem that transition carbides are difficult to sinter [Zou Qin; Li Yanguo; He Wenquan; Li Xiaopu; Xiong Jianchao. Tungsten carbide cemented carbide composite material without metal binder phase and its preparation method: CN109434122A. Yanshan University, published on March 8, 2019]. On the basis of the above patent, the inventor continued to add components to prepare a five-component composite cemented carbide material of TaC, WC, NbC, VC and TiCx. The fracture toughness of the tungsten carbide composite material is 4.96~12.51MPa·m1 / 2, which has good fracture toughness [Zou Qin; Li Yanguo; He Wenquan; Wang Mingzhi; Xiong Jianchao. A tungsten carbide composite material and its preparation method: CN 109485425A. Yanshan University, published on March 19, 2019]. Li Yanguo et al. provide a TiCx-bonded nanocrystalline WC-based cemented carbide composite material and its preparation method. Nano-grade TiCx is mixed with nano-grade tungsten carbide powder, and hot pressing and sintering are used to prepare a TiCx-bonded nanocrystalline WC-based cemented carbide composite material, which overcomes the problem of high sintering temperature of ceramic binder tungsten carbide cemented carbide, while improving its hardness and fracture toughness [Li Yanguo; Zou Qin; Jiao Zijian. TiCx-bonded nanocrystalline WC-based cemented carbide composite material and its preparation method: CN111471908A. Yanshan University, published on July 31, 2020]. At the same time, He Wenquan used TiC 0.4 The effect of C vacancies in non-stoichiometric TiC0.4 on the sinterability of the composites was studied by layering and composite sintering with WC. The effects of WC content, sintering temperature and sintering method on the sinterability of TiC were also studied. 0.4 -WC composite sintered body. The test results show that TiC 0.4 The vacancies in TiC promote sintering. 0.4 When the content is 15 vol.% and the WC content is 85 vol.%, the composite sintered body has the best comprehensive properties at the spark plasma sintering (SPS) temperature of 1600°C. Its Vickers hardness is 22.2 GPa, fracture toughness is 9.6 MPa·m1 / 2, and flexural strength is 612 MPa.

[0003] The preparation methods of TiCx involved in the above-mentioned cemented carbide materials all adopt a two-step method, that is, firstly preparing it through mechanical alloying (MA), and then mixing it with other components and sintering it. The preparation process is complicated and has a long cycle, which increases the production cost. In addition, oxygen is easily introduced during the preparation process, which affects the performance of the sintered body. Summary of the invention

[0004] In view of this, the technical problem to be solved by the present invention is to provide a ceramic-bonded WC cemented carbide and a preparation method thereof, which solves the problem of lack of WC cemented carbide bonded with ceramic in the prior art and high production cost of traditional methods for preparing cemented carbide.

[0005] In order to solve the above technical problems, the present invention discloses a ceramic-bonded WC cemented carbide. The WC cemented carbide powder is prepared by using W, Ti, Zr and C powder raw materials. The mass fraction of W powder is (85-90) wt.%, the mass fraction of Ti powder is (2-2.5) wt.%, the mass fraction of Zr powder is (4-4.5) wt.%, and the mass fraction of C powder is (6-6.5) wt.%.

[0006] Furthermore, the above-mentioned WC cemented carbide powder is prepared by using W, Ti, Zr and C powder raw materials, the mass fraction of W powder is 87.4 wt.%, the mass fraction of Ti powder is 2.2 wt.%, the mass fraction of Zr powder is 4.2 wt.%, and the mass fraction of C powder is 6.2 wt.%; the purity of W powder is 99.9%, and the particle size is 0.6μm or finer, the purity of Ti powder is 99.5%, and the particle size is 48μm or finer, the purity of Zr powder is 99.5%, and the particle size is 3μm or finer, and the purity of C powder is 99.9%, and the particle size is 2.6nm or finer.

[0007] A method for preparing a ceramic-bonded WC cemented carbide comprises the following steps: S1. After adding dispersant to the raw material powders of each preset mass fraction, the powders were placed in a WC carbide ball mill for ball milling. The ball-to-material mass ratio was 20:1, the rotation speed was 450 r / min, the ball milling was performed for 20 hours, each rotation was 30 minutes, and the machine was stopped for 30 minutes for heat dissipation to obtain a mixed powder; S2. Pre-press the mixed powder prepared in step S1, with a pre-pressing pressure of 500 MPa and a pre-pressing time of 60 seconds. Then, the pre-pressed sample is subjected to spark plasma sintering (SPS), with a sintering pressure of 40 MPa, a sintering temperature of 1800°C, and a holding time of 10 minutes. Then, the temperature is lowered and the pressure is released to obtain a ceramic-bonded WC cemented carbide.

[0008] Furthermore, the above-mentioned dispersant is industrial ethanol with a purity of ≥99.7%, and 0.2-0.5 mL of the dispersant is added to every 10 g of powder.

[0009] Furthermore, the specific sintering process and parameters in the above step S2 are: first, slowly apply pressure to the sample to 40MPa; then, heat from room temperature to 600℃ at a heating rate of 100℃ / min, and keep at 600℃ for 5 minutes; then heat from 600℃ to 1800℃ at a heating rate of 100℃ / min, and keep at the terminal temperature for 10 minutes. Cool with the furnace to obtain a blank. The prepared blank is subjected to surface grinding and deburring treatment to obtain a new high-entropy ceramic-bonded WC cemented carbide material.

[0010] Compared with the prior art, the present application can obtain the following technical effects: The present invention adopts a one-step method to mix W powder, Ti powder, Zr powder and C powder respectively in a mechanical alloying (MA) manner, and adopts SPS sintering technology to prepare a new type of high-entropy ceramic-bonded WC cemented carbide composite material. The vacancies in the system are used to reduce the sintering temperature and promote sintering, reduce the introduction of oxygen, and improve the hardness, fracture toughness, corrosion resistance and other properties of the sintered body. At the same time, the process is simplified and the production cost of the cemented carbide material is reduced.

[0011] Of course, any product implementing this application does not necessarily need to achieve all of the technical effects described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings: Figure 1 is the XRD pattern of the WC cemented carbide in Examples 1-3; Figure 2 Surface SEM images of WC cemented carbide in Example 2, wherein the left side is the surface SEM image and the right side is the crack SEM image. DETAILED DESCRIPTION

[0013] The following will describe the implementation methods of the present application in detail with the help of accompanying drawings and examples, so that the implementation process of how the present application uses technical means to solve technical problems and achieve technical effects can be fully understood and implemented accordingly.

[0014] The testing equipment used in the present invention are all instruments used in conventional testing methods, such as X-ray diffractometer, hardness tester, scanning electron microscope, etc. The exemplary embodiments, features and performance aspects of the present invention will be described in detail below.

[0015] The raw material powders of each preset mass fraction were added with dispersant and then put into WC carbide ball mill for ball milling. The ball-to-material mass ratio was 20:1, the rotation speed was 450 r / min, the ball milling was carried out for 20 hours, each rotation was 60 minutes, and the machine was stopped for 30 minutes for heat dissipation to obtain a mixed powder. The prepared mixed powder was pre-pressed with a pre-pressing pressure of 500MPa and a pre-pressing time of 60s. Then, the pre-pressed sample was subjected to SPS sintering with a sintering pressure of 40MPa, a sintering temperature of 1700-1900℃, and a holding time of 10 minutes. Then, the temperature was reduced and the pressure was released to obtain a ceramic-bonded WC carbide. Example 1

[0016] The raw material formula is weighed according to the following mass percentages:

[0017] S1. Add dispersant to the raw material powder composed of the mass fraction in Table 1 and put it into a WC hard alloy ball mill for ball milling. The ball-to-material mass ratio is 20:1, the rotation speed is 450 r / min, and the ball milling is carried out for 20 h. The forward and reverse rotations are alternately operated for 60 min each time, and the machine is stopped for 20 min for heat dissipation to obtain a mixed powder. S2. Pre-press the mixed powder prepared in step S1 with a pre-pressing pressure of 500MPa and a pre-pressing time of 60s. Then, the pre-pressed sample is subjected to SPS sintering with a sintering pressure of 40MPa. The heating system is as follows: first, the temperature is increased from room temperature to 600℃ at a heating rate of 100℃ / min, and kept at 600℃ for 5 min; then the temperature is increased from 600℃ to 1700℃ at a heating rate of 100℃ / min, and kept at this temperature for 10min. Cool with the furnace to obtain a blank. The prepared blank is subjected to surface grinding and deburring treatment to obtain a high-entropy ceramic-bonded WC cemented carbide. The sintered WC cemented carbide sample is ground and polished, and then the microstructure and performance are tested and analyzed. The results show that the density is 97.4%, the hardness is 19.22GPa, and the fracture toughness is 6.9MPa·m 1 / 2 . Example 2

[0018] The raw material formula is weighed according to the following mass percentages:

[0019] S1. Add dispersant to the raw material powder composed of the mass fraction in Table 2, and then put it into a WC hard alloy ball mill for ball milling. The ball-to-material mass ratio is 20:1, the speed is 450 r / min, and the ball milling is carried out for 20 h. The forward and reverse rotations are alternately operated for 60 min each time, and the machine is stopped for 20 min for heat dissipation to obtain a mixed powder. S2. Pre-press the mixed powder prepared in step S1 with a pre-pressing pressure of 500MPa and a pre-pressing time of 60s. Then, the pre-pressed sample is subjected to SPS sintering with a sintering pressure of 40MPa. The heating system is as follows: first, the temperature is increased from room temperature to 600℃ at a heating rate of 100℃ / min, and kept at 600℃ for 5 min; then, the temperature is increased from 600℃ to 1800℃ at a heating rate of 100℃ / min, and kept at 10min. Cool with the furnace to obtain a blank. The prepared blank is subjected to surface grinding and deburring treatment to obtain a high-entropy ceramic-bonded WC cemented carbide. After the sintered WC cemented carbide sample is ground and polished, the microstructure and performance are tested and analyzed. The results show that the density is 98.5%, the hardness is 23.75GPa, and the fracture toughness is 10.7MPa·m 1 / 2 . Example 3

[0020] The raw material formula is weighed according to the following mass percentages:

[0021] S1. Add dispersant to the raw material powders composed of the mass fractions in Table 3 and put them into a WC carbide ball mill for ball milling. The ball-to-material mass ratio is 20:1, the rotation speed is 450 r / min, and the ball milling is carried out for 10 h. The forward and reverse rotations are alternately operated for 60 min each time, and the machine is stopped for 20 min for heat dissipation to obtain a mixed powder. S2. Pre-press the mixed powder prepared in step S1 with a pre-pressing pressure of 500MPa and a pre-pressing time of 60s. Then, the pre-pressed sample is subjected to SPS sintering with a sintering pressure of 40MPa. The heating system is as follows: first, the temperature is increased from room temperature to 600℃ at a heating rate of 100℃ / min, and kept at 600℃ for 5 min; then the temperature is increased from 600℃ to 1900℃ at a heating rate of 100℃ / min, and kept at 10min. Cool with the furnace to obtain a blank. The prepared blank is subjected to surface grinding and deburring treatment to obtain a high-entropy ceramic-bonded WC cemented carbide. The sintered WC cemented carbide sample is ground and polished, and then the microstructure and performance are tested and analyzed. The results show that the density is 98.7%, the hardness is 22.65GPa, and the fracture toughness is 8.4MPa·m 1 / 2 .

[0022] The results of the above examples are analyzed, and it is found that the hard alloy with a raw material sintering temperature of 1800° C. has the best performance. The present invention can prepare WC hard alloy with excellent performance through a simple preparation method.

[0023] The above description shows and describes several preferred embodiments of the present invention, but as mentioned above, it should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the invention concept described herein through the above teachings or the technology or knowledge of the relevant field. Changes and variations made by those skilled in the art do not depart from the spirit and scope of the present invention, and should be within the scope of protection of the claims attached to the present invention.

Claims

1. A ceramic-bonded WC cemented carbide, characterized in that: WC cemented carbide powder is prepared from W, Ti, Zr and C powder raw materials, wherein the mass fraction of W powder is (85-90) wt.%, the mass fraction of Ti powder is (2-2.5) wt.%, the mass fraction of Zr powder is (4-4.5) wt.%, and the mass fraction of C powder is (6-6.5) wt.%.

2. The ceramic-bonded WC cemented carbide according to claim 1, characterized in that: The WC cemented carbide powder is prepared using W, Ti, Zr and C powder raw materials, wherein the mass fraction of the W powder is 87.4 wt.%, the mass fraction of the Ti powder is 2.2 wt.%, the mass fraction of the Zr powder is 4.2 wt.%, and the mass fraction of the C powder is 6.2 wt.%; the purity of the W powder is 99.9%, and the particle size is 0.6 μm or less, the purity of the Ti powder is 99.5%, and the particle size is 48 μm or less, the purity of the Zr powder is 99.5%, and the particle size is 3 μm or less, and the purity of the C powder is 99.9%, and the particle size is 2.6 nm or less.

3. The method for preparing the ceramic-bonded WC cemented carbide according to claim 1, characterized in that: The following steps are involved: S1. After adding dispersant to the raw material powders of each preset mass fraction, the powders were placed in a WC carbide ball mill for ball milling. The ball-to-material mass ratio was 20:1, the rotation speed was 450 r / min, the ball milling was performed for 20 hours, each rotation was 30 minutes, and the machine was stopped for 30 minutes for heat dissipation to obtain a mixed powder; S2. Pre-press the mixed powder prepared in step S1, with a pre-pressing pressure of 500 MPa and a pre-pressing time of 60 seconds. Then, the pre-pressed sample is subjected to spark plasma sintering (SPS), with a sintering pressure of 40 MPa, a sintering temperature of 1800°C, and a holding time of 10 minutes. Then, the temperature is lowered and the pressure is released to obtain a ceramic-bonded WC cemented carbide.

4. The method for preparing ceramic-bonded WC cemented carbide according to claim 3, characterized in that: The dispersant is industrial ethanol with a purity of ≥99.7%, and 0.2 to 0.5 mL of the dispersant is added to every 10 g of powder.

5. The method for preparing ceramic-bonded WC cemented carbide according to claim 3, characterized in that: The specific sintering process and parameters in step S2 are as follows: first, slowly apply pressure to the sample to 40 MPa; then, heat from room temperature to 600°C at a heating rate of 100°C / min, and keep at 600°C for 5 min; then heat from 600°C to 1800°C at a heating rate of 100°C / min, and keep at the terminal temperature for 10 min. Cool with the furnace to obtain a blank. The prepared blank is subjected to surface grinding and deburring treatment to obtain a new high-entropy ceramic-bonded WC cemented carbide material.

Citation Information

Patent Citations

  • Metal-bonding-phase-free carbon tungsten hard alloy composite material and preparation method thereof

    CN109434122A

  • Tungsten carbide composite material and preparation method thereof

    CN109485425A

  • TiC<x> combined nanocrystalline WC-based hard alloy composite material and preparation method thereof

    CN111471908A

Cited By

  • Metal-high-entropy ceramic composite combined WC hard alloy and preparation method thereof

    CN122279349A

  • Non-stoichiometric ratio compound oxide synergistically reinforced and toughened WC hard alloy and preparation method thereof

    CN122380877A